Paediatric cerebrovascular CT angiography—towards better image quality - Thust, Stefanie C.; Chong, Wui Khean Kling; Gunny, Roxana; Mazumder, Asif; Poitelea, Marius; Welsh, Anna; Ederies, Ash; Mankad, Kshitij (Quantitative Imaging in Medicine and Surgery, 2014)
Background: Paediatric cerebrovascular CT angiography (CTA) can be challenging to perform due to variable cardiovascular physiology between different age groups and the risk of movement artefact. This analysis aimed to determine what proportion of CTA at our institution was of diagnostic quality and identify technical factors which could be improved. Materials and methods: a retrospective analysis of 20 cases was performed at a national paediatric neurovascular centre assessing image quality with a subjective scoring system and Hounsfield Unit (HU) measurements. Demographic data, contrast dose, flow rate and triggering times were recorded for each patient. Results: Using a qualitative scoring system, 75% of studies were found to be of diagnostic quality (n=9 ‘good’, n=6 ‘satisfactory’) and 25% (n=5) were ‘poor’. Those judged subjectively to be poor had arterial contrast density measured at less than 250 HU. Increased arterial opacification was achieved for cases performed with an increased flow rate (2.5-4 mL/s) and higher intravenous contrast dose (2 mL/kg). Triggering was found to be well timed in nine cases, early in four cases and late in seven cases. Of the scans triggered early, 75% were poor. Of the scans triggered late, less (29%) were poor. Conclusions: High flow rates (>2.5 mL/s) were a key factor for achieving high quality paediatric cerebrovascular CTA imaging. However, appropriate triggering by starting the scan immediately on contrast opacification of the monitoring vessel plays an important role and could maintain image quality when flow rates were lower. Early triggering appeared more detrimental than late.